A paisagem do Complexo Arqueológico Morro do Caracará no Parque Nacional do Pantanal Mato-grossense - Garcia, Gabriele Viega (2014)
The Archaeological heritage, considered a property of the Union, is a cultural memories of all humanity and of the human groups, and the use of it is protected by the Federal Constitution, Federal Laws, Decrees and Ordinances. Evaluated as finite resource and not renewable, the occurrence of it in Conservation Units, principally on the category of Integral Protection, made the Morro do Caracará Archaeological Complex, that is on the Pantanal Matogrossense National Park, a eligible place for study, because it has a archaeological importance. Were done primary and secondary surveys with the intent of identifying and analyzing the archaeological potential of the Morro do Caracará, with the objective to contribute to the Management Plan and indication for to become a listed heritage, as a way to ensure the integrity of the sites located there. To reach the target set, were analyzed the archaeological potential and cultural of the Morro do Caracará and other places, with the adoption of bias of the cultural geography and the archaeology of landscape to prepare some notes about cultural landscape, archaeological monument, public use and conservation.